THE INFLUENCE OF ORGANIZATIONAL CULTURE, COMPETENCE, AND WORK ENVIRONMENT ON THE PERFORMANCE OF TEACHERS AT SMP MUHAMMADIYAH 13 MAKASSAR - Adisaputra, Whisnu (Siddiq Institute, 2023)
The purpose of this study is to examine, analyze, and interpret the influence of Organizational Culture, Competence, and Work Environment on the performance of teachers at SMP Muhammadiyah 13 Makassar. This research is of a quantitative descriptive nature, with a population and sample of 31 teachers. Data collection methods include interviews, questionnaires, and literature review. The research data will be analyzed using statistical tools with SPSS 24 software. The results of the study indicate that: 1. Organizational Culture has a positive and significant impact on the performance of teachers at SMP Muhammadiyah 13 Makassar. Generally, Organizational Culture has a strong influence on improving teacher performance, which is crucial for achieving the organization's goals. 2. Competence has a positive and significant impact on the performance of teachers at SMP Muhammadiyah 13 Makassar. Competence is a crucial factor that supports teachers in developing their skills and knowledge to the fullest extent to contribute to the organization's goals consciously. 3. Work Environment also has a positive and significant impact on the performance of SMP Muhammadiyah 13 Makassar. The main factors in the work environment include the atmosphere and supporting facilities, which play a vital role in carrying out teachers' tasks.